Peningkatan Produktivitas Dengan Metode Green Productivity Pada PT. Bangun Tenera Riau Desa Pantai Raja Kabupaten Kampar - Fahrul Rozi Adami Nasution; Meri Andriani; Yusnawati (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2023)
PT Bangun Tenera Riau is a company engaged in the processing of oil palm fresh fruit bunches, located in Pantai Raja Village, Perhentian Raja District, Kampar Regency, Riau Province. The problem faced by PT Bangun Tenera Riau is that the company has not maximally utilized the by-products produced in the form of waste. This research aims to improve the production process by selecting alternative solutions to increase and enhance the initial green productivity index value so that productivity can increase and the impact on the environment can be reduced. The method used in this research is the green productivity method. Based on the environmental performance indicator (EPI) calculation, it is known that the value of biological oxygen demand (BOD) liquid waste has a deviation of -0.63% and an EPI value of -0.16 which exceeds the waste quality standard based on Kep-51 / MENLH / 1995 so that it is necessary to improve the quality of waste through alternative solutions. The alternative solution chosen is an anaerobic biogas reactor and rotating biological contactor (RBC) used to improve waste quality and company productivity. The study's results using the green productivity method obtained an average final total productivity of 1.31 with the initial value of the average productivity in each month being 1.17. The productivity value of the company increased by 0.21 with the efficiency of improving the quality of waste by BOD by 96.81% and converting liquid waste into biogas which is beneficial to the community